West of Jim Crow : The Fight against California's Color Line - Hudson, Lynn M. (Lynn Maria), 1961- (Book collections on Project MUSE., 2020)
"African Americans who moved to California in hopes of finding freedom and full citizenship instead faced all-too-familiar racial segregation. As one transplant put it, "The only difference between Pasadena and Mississippi is the way they are spelled." From the beaches to streetcars to schools, the Golden State-in contrast to its reputation for tolerance-perfected many methods of controlling people of color. Lynn M. Hudson deepens our understanding of the practices that African Americans in the West deployed to dismantle Jim Crow in the quest for civil rights prior to the 1960s. Faced with institutionalized racism, black Californians used both established and improvised tactics to resist and survive the state's color line. Hudson rediscovers forgotten stories like the experimental all-black community of Allensworth, the California Ku Klux Klan's campaign of terror against African Americans, the bitter struggle to integrate public swimming pools in Pasadena and elsewhere, and segregationists' preoccupation with gender and sexuality"--